2002
DOI: 10.1200/jco.20.6.1657
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Finding and Pharmacokinetic Study of Cisplatin, Gemcitabine, and SU5416 in Patients With Solid Tumors

Abstract: The incidence of thromboembolic events, possibly related to the particular regimen tested in this study, discourages further investigation of this regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(116 citation statements)
references
References 48 publications
6
107
2
1
Order By: Relevance
“…These data suggest that differences between the dividing tumor-associated endothelial cells and quiescent endothelial cells provide an opportunity for selective therapeutic intervention. However, in clinical trials with agents that target VEGF, hemorrhage and thrombosis have been observed as complications that may have been due in part to disruption of the normal vascular integrity (8). Furthermore, although our data with ZD6474 suggest that the quiescent vasculature of the lung may not be targeted, the interface between normal lung and tumor vasculature may be targeted.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…These data suggest that differences between the dividing tumor-associated endothelial cells and quiescent endothelial cells provide an opportunity for selective therapeutic intervention. However, in clinical trials with agents that target VEGF, hemorrhage and thrombosis have been observed as complications that may have been due in part to disruption of the normal vascular integrity (8). Furthermore, although our data with ZD6474 suggest that the quiescent vasculature of the lung may not be targeted, the interface between normal lung and tumor vasculature may be targeted.…”
Section: Discussioncontrasting
confidence: 43%
“…Bevacizumab, a humanized antibody against VEGF, has shown great promise and improved survival for patients with metastatic colorectal or lung cancer when used in combination with chemotherapy (6,7). However, although survival was improved in these studies, there remains an unmet need for improved efficacy, and clinical trials with VEGF inhibitors have been associated with thromboembolic and hemorrhagic complications (8).…”
Section: Introductionmentioning
confidence: 99%
“…According to such reported values, a significant area of the synergistic interaction between these two drugs occurs in the range of clinically achievable concentrations. Importantly, a similar analysis also suggested that the predominant additive profile obtained from the combination of CIGB-300 plus cisplatin in cervical cancer cells occurs in a concentration range achievable in vivo for CIGB-300 (<30 ”M) and cisplatin (<15 ”M) (30,31).…”
Section: Discussionmentioning
confidence: 84%
“…Although some clinical activity was recorded, and DEMRI analysis revealed a reduction in tumour vascular permeability, biological activity could not be demonstrated by means of consistent changes in the serum markers of endothelial cell proliferation. In phase I and II combination trials, SU5416 could be given safely in combination with 5-FU and leucovorin, but combining SU5416 with cisplatinum and gemcitabine yielded an unexpectedly high number of severe thromboembolic complications, leading to premature closing of the study (Kuenen et al, 2002a). Randomised phase III studies of SU5416 with 5-FU/ leucovorin and 5-FU/leucovorin/irinotecan in patients with metastatic colorectal carcinoma failed to show a survival benefit of the SU5416 containing regimens, resulting in the cessation of further development of this compound.…”
Section: Vegf Receptor Tyrosine Kinase Inhibitorsmentioning
confidence: 99%